The Impact of Obesity on Thyroid Autoimmunity and Dysfunction: A Systematic Review and Meta-Analysis - Song, Rong-hua; Wang, Bin; Yao, Qiu-ming; Li, Qian; Jia, Xi; Zhang, Jin-an (Frontiers in Immunology, 2019)
Background: To help inform decision making in the clinical setting, we carried out a systematic review and meta-analysis to estimate the association of thyroid disease risks with obesity. Methods—Pubmed, Embase, Web of Science, Cochrane database and Google Scholar electronic databases were searched from inception to October 31, 2018 without language restrictions to explore the relationship between thyroid disorders and obesity. The relative risk (RR) or odds risk (OR) for thyroid disorders were pooled using the SPSS and STATA software. Results—A total of 22 studies were included in the study. 1) Meta-analysis showed that obesity is significantly associated with increased risk of hypothyroidism (RR=1.86, 95%CI 1.63–2.11, P<0.001). Meta-analyses after stratification further showed that obese population had increased risks of overt hypothyroidism (RR=3.21, 95%CI 2.12–4.86, P<0.001) and subclinical hypothyroidism (RR=1.70, 95%CI 1.42–2.03, P<0.001). 2) Further meta-analysis also showed obesity was clearly associated with Hashimoto's thyroiditis (RR=1.91, 95%CI 1.10–3.32, P=0.022), but not Graves’ disease. 3) In the meta-analysis of antibodies, obesity was correlated with positive thyroid peroxidase antibody (TPOAb) (RR=1.93, 95%CI 1.31–2.85, P=0.001), but not positive thyroglobulin antibody (TGAb). Conclusions: Obesity was significantly related to hypothyroidism, HT and TPOAb, implying that prevention of obesity is crucial for thyroid disorders.